A critical analysis of the direct effects of dredging on fish. Issue 5 (27th March 2017) - Wenger, Amelia S.; Harvey, Euan; Wilson, Shaun; Rawson, Chris; Newman, Stephen J.; Clarke, Douglas; Saunders, Benjamin J.; Browne, Nicola; Travers, Michael J.; Mcilwain, Jennifer L.; Erftemeijer, Paul L. A.; Hobbs, Jean‐Paul A.; et al.
Abstract: Dredging can have significant impacts on aquatic environments, but the direct effects on fish have not been critically evaluated. Here, a meta‐analysis following a conservative approach is used to understand how dredging‐related stressors, including suspended sediment, contaminated sediment, hydraulic entrainment and underwater noise, directly influence the effect size and the response elicited in fish across all aquatic ecosystems and all life‐history stages. This is followed by an in‐depth review summarizing the effects of each dredging‐related stressor on fish. Across all dredging‐related stressors, studies that reported fish mortality had significantly higher effect sizes than those that describe physiological responses, although indicators of dredge impacts should endeavour to detect effects before excessive mortality occurs. Studies examining the effects of contaminated sediment also had significantly higher effect sizes than studies on clean sediment alone or noise, suggesting additive or synergistic impacts from dredging‐related stressors. The early life stages such as eggs and larvae were most likely to suffer lethal impacts, while behavioural effects were more likely to occur in adult catadromous fishes. Both suspended sediment concentration and duration of exposure greatly influenced the type of fish response observed, with both higher concentrations and longer exposure durations associated with fish mortality. The review highlights the need for in situ studies on the effects of dredging on fish which consider the interactive effects of multiple dredging‐related stressors and their impact on sensitive species of ecological and fisheries value. This information will improve the management of dredging projects and ultimately minimize their impacts on fish.